SPATIAL DYNAMICS OF ATLANTIC FOREST FRAGMENTS IN A RIVER BASIN - Lopes, Elfany Reis do Nascimento; de Sousa, Jocy Ana Paixão; de Souza, José Carlos; Albuquerque Filho, José Luiz; Lourenço, Roberto Wagner (Floresta, 2019)
Considering the intrinsic relationship between vegetation and conservation of water resources, we evaluated the natural vegetation of an Atlantic Forest fragment through landscape metrics and spectral vegetation indices, indicating ways for its conservation in the Una river basin, Ibiúna, São Paulo, Brazil. We analyzed landscape metrics and the extraction of mean altitude, slope, and distance from the drainage network for each fragment based on the vectors of forest fragments in the river basin, using ArcGis 10.3. Normalized difference vegetation indices, photochemical production, and carbon flux were estimated by combining red, green, blue, and infrared spectral bands near the RapidEye satellite image. The results showed 197 fragments with sizes ranging from 1 to 306 hectares and irregularly shaped. The largest fragments are few in number, but account for 52% of the river basin's vegetation cover area. The vegetation presented high levels of biomass but moderate photosynthetic production, coinciding for a moderate carbon flux. The best scores were related to fragments at higher altitudes, in sloping areas next to drainage sites. Actions to conserve the fragments of larger areas and draw up environmental awareness measures should be encouraged, since high agricultural vocation may incite the reduction of these areas to increase economic production.